The boyfriend [large type] - McFadden, Freida (Thorndike Press large print dynamic drama., 2024)
"Sydney Shaw, like every single woman in New York, has terrible luck with dating. But finally, she hits the jackpot. Her new boyfriend is utterly perfect. He's charming, handsome, and a doctor. Then the brutal murder of a young woman - the latest in a string of deaths across the coast - confounds police. The primary suspect? A mystery man who dates his victims before he kills them. Sydney should feel safe. After all, she is dating the guy of her dreams. But she can't shake her own suspicions that the perfect man may not be as perfect as he seems. Because someone is watching her every move, and if she doesn't get to the truth, she'll be the killer's next victim." --